RIAP DIAMETER DARI TANAMAN NON-LEGUM DI AREA REKLAMASI DAN REVEGETASI PT ADARO INDONESIA, PROVINSI KALIMANTAN SELATAN, INDONESIA - Muhammad Noor Isnaini; Mochamad Arief Soendjoto; Syam’ani Syam’ani (Jurnal Sylva Scienteae, 2020)
There is no data on diameter increment of non-legume plants growing, especially in the reclamation and revegetation areas of the former mining area. This study aimed to calculate the diameter increment, current average increment (CAI), and annual average increment (MAI) of non-legume plants in the reclamation and revegetation area of PT Adaro Indonesia, which operates in Kalimantan Selatan Province, Indonesia. The results of this study can be used by this company to regenerate or embroider vegetation so that vegetation can provide ecological functions in a sustainable manner. In 10 (10 x 20) m2 measuring plots, the circumference of the breast height of woody plants at the pole and tree levels was measured in three measurement periods (December 2016, May 2017, and December 2017). The circumference was converted so that a diameter at breast height was obtained. From this measurement the increment and diameter growth obtained are as follows. Of the six non-legume plant species found and meeting the criteria of poles and trees, only gmelina and jabon could be calculated for increment and diameter growth. The increment and growth of diameter of balik angin, kapok randu, eucalyptus, and alaban were not counted by species because the number of individuals each species was very small, but it was calculated in a combined form with gmelina and jabon so that it become increment and growth of non-legume diameter. The diameter increment over the three measurement periods and the current annual increment (CAI) of gmelina are lower than that of jabon and also non-legume. On the contrary, according to its mean annual increment (MAI), gmelina is higher than jabon and non-legume.Keywords : diameter increment; growth; non-legume; reclamation; coal-mining